Investigation of Wei (protective), Qi (vital), Ying (nutritive), and Xue (blood) syndromes according to traditional medicine in patients with dengue hemorrhagic fever - Le, Thi Kim Quy; Le, Cong Hau; Nguyen, Thien Phuoc (Tạp chí Y Dược Huế, 2025)
Background: Sepsis remains a leading cause of hospital mortality worldwide, placing significant pressure on healthcare systems. Therefore, investigating severe prognostic factors in patients with sepsis is crucial for improving prevention and treatment outcomes. Objective: To describe clinical and laboratory characteristics and evaluate severe prognostic factors for severity and mortality in patients with sepsis. Methods: A cross-sectional descriptive study was conducted on 107 patients admitted to the Intensive Care Unit (ICU) at Hue Central Hospital from September 2024 to November 2024. Data were collected from medical records and patient/relative interviews. Statistical analysis included Receiver Operating Characteristic (ROC) curves to determine the Area Under the Curve (AUC) for prognostic factors. Results: The mean age was 64.44 ± 15.75 years. The incidence of septic shock was 60.7% (65/107), and the mortality rate was 48.6% (52/107). Regarding prognostic factors for severity: Procalcitonin (PCT) at a cutoff of 7.012 ng/mL had a sensitivity of 89.2% and specificity of 78.2%; Lactate at a cutoff of 2.395 mmol/L had a sensitivity of 93.8% and specificity of 78.6%. Regarding mortality prediction: The SOFA and APACHE II scores showed significant predictive value, with SOFA (AUC 0.907) demonstrating high specificity (98.2%) for mortality risk. Conclusion: PCT and blood lactate levels are valuable for predicting severe outcomes in sepsis patients. Furthermore, the SOFA and APACHE II scoring systems are useful in predicting progression to septic shock and mortality in the study population.